The effect of the transition to IFRS on the value judgement of investors - Alexandra Szekeres; Gergő Tömöri (Competitio)
In our research, we examined the profitability of companies switching to IFRS and the value judgement of investors in the two accounting systems. During the examination, we established that there is no significant difference in the ROS and ROA profitability indicators in the two accounting systems. It is important to note that in the case of both indicators, for companies with a high fixed asset requirement, there is a significant difference in the two accounting systems based on the results of the Wilcoxon rank sum test. Taking into account the number of elements of the clusters, their proportion, and the value of the effect size, in our opinion, the conclusion cannot be drawn for the entire basic population that the indicators significantly differed as a result of the transition, because the difference can only be observed in the cluster with a lower number of elements, or a particularly strong relationship cannot be revealed for any of the indicators. On the other hand, for the ROE indicator, a significant difference can be clearly established in the two accounting systems, as the significant relationship can be demonstrated both in companies with low and high capital requirements. Overall, in the IFRS, the companies showed more favourable profitability with regard to the ROE indicator. The second examination of our research is related to this, which aimed to determine whether the significant deviation of the ROE indicator in the year of the transition can be attributed to the transition to IFRS.